(untitled) (The Review of Diabetic Studies, 2025)
Background: Diabetic ketoacidosis (DKA) remains a critical medical emergency with high morbidity and mortality in intensive care units (ICUs). Advances in resuscitation fluids, insulin infusion protocols, and supportive interventions have prompted a reassessment of contemporary management strategies. Objective: This systematic review aimed to evaluate the effectiveness of modern DKA treatment protocols—including fluid resuscitation, insulin administration, and novel ICU-based strategies—on clinical and biochemical outcomes. Methods: Following PRISMA 2020 guidelines, ten peer-reviewed studies published between 2010 and 2024 were analyzed. Data were extracted from randomized controlled trials, cohort studies, and international surveys assessing outcomes such as time to DKA resolution, acid–base normalization, electrolyte correction, and adverse events. Results: Balanced crystalloids, compared to normal saline, consistently reduced hyperchloremic metabolic acidosis (chloride difference: 5–8 mmol/L; bicarbonate increase: 2–3 mmol/L) and shortened DKA resolution by 20–30%. Insulin infusion strategies revealed no significant difference in resolution time between fixed and variable rates; however, fixed rates increased severe hypoglycemia (50% vs. 13%). Tele-ICU pharmacist interventions and standardized pediatric protocols improved time to recovery and safety outcomes. Conclusion: Balanced crystalloids and standardized insulin protocols optimize DKA management in ICUs, enhancing metabolic correction and patient safety. Future multicenter trials should refine fluid choice, insulin titration, and telemedicine integration for protocolized care.